PENGARUH PENGUJIAN KEKERASAN DAN PENGUJIAN TEKAN TERHADAP KARAKTERISTIK GAYA TUMBUKAN PADA CANGKANG KENARI (CANARIUM INDICUM L) - Loppies, Leslie S.; Patty, Alexander A.; Pelasula, Berthy; Lekatompessy, Roy R.; Nanulaitta, Nevada Mario (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Kenari (Canarium indicum L) belongs to the Burseraceae family and is one of the endemic fruits in Indonesia, especially Maluku. Walnuts have a tough shell that encloses the flesh, to get the flesh without damaging it careful effort is needed. This study investigated the strength of walnut shells through mechanical testing to determine the amount of impact force needed to break the walnut shell. The mechanical test carried out is a compression test and impact test. The values of these tests assist in determining, measuring, and analyzing the minimum and maximum force loads required to crack a walnut shell. Tests were carried out on walnut shells from 6 different villages on Ambon Island and Saparua Island. The impact test where the highest impact absorption energy value was found in walnut shells from Booi Village, namely 23.18 J/mm2, and the lowest in walnut shells from Morela Village, 22.40 J/mm2. In the compression test where the lowest value was found in walnut shells from Morela village with a value of 3.61 MPa while the highest value was found in walnut shells from Booi village, namely 5.24 MPa. Whereas the minimum compressive force is 16.22 kgf/mm2 and the maximum compressive force is 17.61 kgf/mm2.